Predictive pulse-pattern current modulation scheme for harmonic reduction in three-phase multidrive systems - Davari, P.; Yang, Y.; Zare, Firuz; Blaabjerg, F. (Institute of Electrical and Electronic Engineers, 2016)
© 1982-2012 IEEE. The majority of the industrial motor drive systems are equipped with the conventional line-commutated front-end rectifiers and being one of the main sources of harmonics in the power line. While a parallel combination of these drive units elevates current quality issues, a proper arrangement of them can lead to the cancellation of specific harmonics. This paper proposes a new cost-effective harmonic mitigation solution for multidrive systems using a predictive pulse pattern current modulation control strategy. The proposed technique applies suitable interaction among parallel drive units at the rectification stage to synthesize sinusoidal input currents. The input voltage sensing is avoided in order to minimize the number of required sensors, and the grid synchronization also has been implemented based on a common phase-locked loop (PLL) using the dc-link capacitor voltage ripple. Experimental results validate the effectiveness of the proposed strategy.